VD_FINDINFO Jug / 2016 / 75 vom 3. November 2015 - VD Tribunal cantonal (2015)
TRAVAIL D'INTÉRÊT GÉNÉRAL, VIOLATION D'UNE OBLIGATION D'ENTRETIEN, RÉVOCATION DU SURSIS, PROLONGATION | 217 CP, 37 CP, 46 al. 2 CP, 47 CP